The Impact of Neuroscience-Based Modern Islamic Education on the Aspect of Creative Imagination and Development of Religious Moderation on Madura Island - Mohammad Jailani; Suyadi Suyadi (Islam Transformatif : Journal of Islamic Studies, 2022)
The fading of Islamic education in Pamekasan is explicitly in remote villages. The decline in Islamic education on Pamekasan Island in the Modern Era, especially in urban areas and remote villages. This is due to the fact that Islamic education in Madura still adopts Islamic boarding school-based education. The need for the development of Islamic education such as religious moderation and the use of information technology, strengthening knowledge management for educators, ustadz, and teachers in Pamekasan Madura. The purpose of this study was to analyse the development of Islamic education on the island of Madura. This study used a field research approach, with the informants being the Pamekasan community, santri, students, teachers, lecturers, and community leaders. Data were collected by observation, in-depth interviews, and documentation. The results of the study proved that the Madurese follow the concepts and alternative approaches to knowledge based on modern Islam. Knowledge and approaches in the technological era are quite accepted by young people, the younger generation, and adults. The neuroscience approach that is packaged with modern Islamic education is able to provide awareness and technology literacy in the Madurese community. One of them is more sensitive and aware of the importance of Islamic education.